Dynamics of Dismissal of Regional Heads in Lampung Province Perspective of Law and Fiqh Siyasah - Zuhraini, Zuhraini; Zaelani, Abdul Qodir; Mu’in, Fathul (IAIN Manado, 2023)
This research aims to determine the impeachment or dismissal of regional heads in Lampung Province from the perspective of Law and Islamic jurisprudence. This problem is interesting to research. Since this province was founded, at least five regional heads have been dishonorably dismissed for committing Corruption, namely the Regent of South Lampung, the Regent of North Lampung, the Regent of Tanggamus, the Regent of Mesuji and the Regent of Central Lampung. This research uses a library study method, is descriptive-analytical, and uses primary and secondary legal data sources, which are then analyzed using the comparative method. This research concluded that the impeachment of regional heads in Lampung Province was carried out because they violated their oath of office, namely committing Corruption as regulated in Law Number 9 of 2015 concerning Regional Government, which is the second amendment to Law Number 23 of 2014 concerning regional government. Corruption in Indonesia is an extraordinary crime because it has a significant and widespread impact. Instead, the budget for regional development and people's welfare is taken for their interests. In Fiqh Siyasah, this issue is included in siyasah qadhaiyah. Every community must obey the laws and regulations. So, if a regional head violates the Law, he can be dishonorably dismissed for acting wickedly and unjustly. The corrupt behavior of regional heads includes sinful acts and forms of cruelty by leaders toward their people.